Benefits Of Yoga In Pregnancy: Systematic Review - Juliana, Mutia; Nainggolan, Lenny; Reffita, Lea Ingne; Kariyadi, Kariyadi; Hitijahubessy, Christy Natalia Magdalena; Hanifah, Astin Nur (International Journal of Health Sciences, 2023)
Introduction: Previous research has shown that yoga therapy can be practiced by pregnant women and provides many benefits. It is not clear when yoga was first introduced as a prenatal practice or the current prevalence of yoga practice among pregnant women. Objective: This article will discuss the benefits of yoga in pregnancy. Methods: This article was prepared using the standards set by Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study shows that it meets all the requirements and the research is up to date. The publications involved were those published between 2013 and 2023. Several different online resources, such as Pubmed and SagePub, were used to do this. Results: We retrieved 108 articles from the PubMed database, while our search results on SagePub returned 87 articles. Search results conducted in 2013 returned a total of 45 articles for PubMed and 32 articles for SagePub. In the end, we compiled a total of 28 papers, of which 18 were from PubMed and 10 were from SagePub. We included nine studies which met the criteria. Conclusions: Previous research has shown that yoga can provide benefits in terms of reducing the incidence of depression, anxiety, and pain during labor.